Randomized Clinical Trial of the Need for Antibiotic Treatment for Low-Risk Catheter-Related Bloodstream Infection Caused by Coagulase-Negative Staphylococci - Laia Badia-Cebada; João Carmezim; María-Teresa; Elena Bereciartua; Luis-Eduardo López; Marta Represa Montenegro; Virginia Pomar; Marta Andrés; Elizabet Petkova; Nieves Sopena; Jaime Lora-Tamayo; Víctor Monsálvez; et al. (MDPI AG, 2023)
According to clinical guidelines, the management of catheter-related bloodstream infections (CRBSI) due to coagulase-negative staphylococci (CoNS) includes catheter removal and antibiotic treatment for 5 to 7 days. However, in low-risk episodes, it remains uncertain whether antibiotic therapy is necessary. This randomized clinical trial aims to determine whether the non-administration of antibiotic therapy is as safe and effective as the recommended strategy in low-risk episodes of CRBSI caused by CoNS. With this purpose, a randomized, open-label, multicenter, non-inferiority clinical trial was conducted in 14 Spanish hospitals from 1 July 2019 to 31 January 2022. Patients with low-risk CRBSI caused by CoNS were randomized 1:1 after catheter withdrawal to receive/not receive parenteral antibiotics with activity against the isolated strain. The primary endpoint was the presence of any complication related to bacteremia or to antibiotic therapy within 90 days of follow-up. The secondary endpoints were persistent bacteremia, septic embolism, time until microbiological cure, and time until the disappearance of a fever. EudraCT: 2017-003612-39 INF-BACT-2017. A total of 741 patients were assessed for eligibility. Of these, 27 were included in the study; 15 (55.6%) were randomized to the intervention arm (non-antibiotic administration) and 12 (44.4%) to the control arm (antibiotic therapy as per standard practice). The primary endpoint occurred in one of the 15 patients in the intervention group (septic thrombophlebitis) and in no patients in the control group. The median time until microbiological cure was 3 days (IQR 1-3) in the intervention arm and 1.25 days (IQR 0.5-2.62) in the control arm, while the median time until fever resolution was zero days in both arms. The study was stopped due to the insufficient number of recruited patients. These results seem to indicate that low-risk CRBSI caused by CoNS can be managed without antibiotic therapy after catheter removal; efficacy and safety are not affected.